(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Arthritis is the condition which is associated with inflammation of a joint, pain, swelling, and stiffness. Drug delivery to the target site remains a challenge due to ineffective drug delivery system. An attempt has been made to formulate and evaluate micro-emulgel for the effective drug delivery in the treatment of Arthritis. Micro-emulgel was loaded with Curcumin and Tinospora cordifolia to enhance bioavailability of extracts which have been widely used in the treatment of arthritis. Micro-emulgel was prepared by emulsion-solvent diffusion method using carbopol 940P as a gelling agent. Micro-emulsion was formulated using Liquid paraffin oil as oil phase; Tween 80 and Span 20 as surfactant and co-surfactant respectively. FTIR studies proved the compatibility between drug, excipient and carbopol. The Prepared micro-emulgel was subjected to various parameters such as pH, rheological studies, spreadability, thermodynamic stability tests, drug content, electro conductivity, and in-vitro release studies. The pH of all formulations was found near to the skin pH value. Viscosity and spreadability of F1 optimized formulation was found to be 146.5×103 cPs and 2.24 g×cm. From the in vitro drug release study, it was revealed that sustained release of formulation last up to 18 hours. F1 formulation showed the highest drug release of Curcumin (92.37%) and Tinospora cordifolia (90.75%). SEM images showed the diameter of oil globules of Micro-emulgel were in range of 1.50 to 2.13µm. Drug release kinetics showed the zero order drug release from the optimized F1 formulation. From the stability studies, F1 formulations had an excellent physical stability.